Novel Therapeutic Strategies Targeting Molecular Pathways of Cystogenesis in Autosomal Polycystic Kidney Disease - Maurizio Salvadori; Aris Tsalouchos (Journal of Renal and Hepatic Disorders, 2017)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease that results from mutations in PKD1 or PKD2. The disease is characterized by the progressive development of fluid-filled cysts derived from renal tubular epithelial cells that destroy the architecture of the renal parenchyma and lead to kidney failure. Until recently, the causes and the molecular pathways that lead to cystogenesis remained obscure. In the last decade, enormous progress has been made in understanding the pathogenesis of ADPKD and the development of new therapies. The purpose of this review is to update on the promising therapies that are being developed and tested based on knowledge of recent advances in molecular and cellular targets involved in cystogenesis.